2022
DOI: 10.3390/horticulturae8030186
|View full text |Cite
|
Sign up to set email alerts
|

Low R/FR Ratio Affects Pakchoi’s Growth and Nitrate Content under Excess Nitrate Stress

Abstract: Nitrate accumulation is one of the main factors of secondary soil salinization in protected horticulture in China. Previous studies have shown that a low red(R)/far-red (FR) ratio can improve the salt tolerance of plants under NaCl stress. However, the effect of a low R/FR ratio on plant growth under nitrate stress is not clear. In order to explore the effect of a low R/FR ratio on the adaptability of pakchoi under high nitrogen stress, the growth index, soluble protein content, soluble sugar content, nitrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The effects of light quality on plant growth and stress tolerance have been widely studied, with research indicating that different light qualities can impact plant tolerance to various types of abiotic stress. For example, studies have shown that the red-to-far-red light (R:FR) ratio can influence plant growth and stress tolerance, with low ratios being associated with improved photosynthetic efficiency and alleviated growth inhibition under stress conditions such as salt, cold, and calcium nitrate stress [ 45 , 46 , 47 , 48 ]. This suggests that light quality may play a role in regulating photosynthesis activity and subsequently affect plant stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of light quality on plant growth and stress tolerance have been widely studied, with research indicating that different light qualities can impact plant tolerance to various types of abiotic stress. For example, studies have shown that the red-to-far-red light (R:FR) ratio can influence plant growth and stress tolerance, with low ratios being associated with improved photosynthetic efficiency and alleviated growth inhibition under stress conditions such as salt, cold, and calcium nitrate stress [ 45 , 46 , 47 , 48 ]. This suggests that light quality may play a role in regulating photosynthesis activity and subsequently affect plant stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…One seedling per pot was incubated in an artificial climate chamber for 25 days with a 2 day irrigation cycle (photoperiod: 12 h; light intensity: 25,000 lx; temperature: 25 °C; humidity: approximately 75%). 26 2.2. Pakchoi Treatment with Profenofos.…”
Section: Plant Materialmentioning
confidence: 99%
“…In addition, the ratio of R:FR affects the photomorphogenesis of plants, and alleviates the damage to plants caused by salt [ 11 ] and cold tolerance [ 12 ]. Previous research by our team found that plants grown under low R:FR ratios showed alleviated growth inhibition [ 3 ]; in pakchoi [ 13 ] under calcium nitrate stress, it effectively improved the photosynthetic efficiency. However, the molecular mechanism of low R:FR in improving the salt resistance of tomato plants is still unclear.…”
Section: Introductionmentioning
confidence: 99%